Evolution of magnetic and structural properties of MgO thin film with vacuum annealing. Issue 1 (1st February 2022) - Vardhan, Harsh; Sharma, Gagan; Sharma, Kavita; Choudhary, R.J.; Phase, D. M.; Gupta, Mukul; Raghavendra Reddy, V.; Gupta, Ajay
Abstract: In this work, investigation of MgO thin film, deposited via e-beam evaporation is carried out with increasing annealing temperature. Structural properties, as elucidated using X-ray based techniques viz. grazing incidence XRD and X-ray reflectivity were associated with magnetic properties of film as observed using superconducting quantum interference device (SQUID) magnetometer. As-deposited film is polycrystalline in nature and exhibits ferromagnetism, which is attributed to presence of Mg vacancies. Vacuum annealing results densification of film with concurrent increase in electron density and reduction in film thickness and saturation magnetization. However, at sufficiently high temperature, electron density and saturation magnetization decreases comparative to as-deposited film. The results are significant for the optimization of desired functional properties of MgO particularly in MgO based magnetic tunnel junctions, providing high tunnel magnetoresistance ratio.